Prevalence of mental disorders is higher in patients with multiple sclerosis than in the general population or in patients with rheumatoid arthritis in France. Issue 3 (August 2020) - Guilleux, Alice; Roux, Jonathan; Travers, David; Leray, Emmanuelle
Background: Mental disorders (MDs) in multiple sclerosis (MS) patients decreases treatment adherence and quality of life, and increases the risk of disability progression and care consumption. Objective: This study was to assess the prevalence of MDs in MS patients compared with healthy controls (HC) of the French general population and rheumatoid arthritis (RA) patients. Methods: The 2015 prevalence of MDs for MS patients, RA patients and general population was estimated using a random population-based data sample from 'National Inter-Scheme Information System on Health Insurance' in the 2011–2015 period. Two control groups (1:5 ratio for the HC and 1:1 for the RA group) were matched to the MS group for year of birth, gender, area of residence and health insurance scheme. Results: A total of 1145 MS patients were identified (sex ratio of 2.5 (F/M); median age 50 years). The prevalence of MDs was higher in the population of patients with MS (37.3%) than in the French general population (13.6%), and to a lesser extent in the RA group (21.1%) leading to the prevalence ratios of 2.8 (95% confidence intervals (CIs) 2.5–3.0) and 1.9 (95% CI 1.7–2.3), respectively. Conclusions: This study confirmed that MS patients are at a higher risk of MDs than the French general population or RA patients.